Impaired Thymic Output in Patients with Chronic Hepatitis C Virus Infection. (12th September 2013) - Hartling, H. J.; Gaardbo, J. C.; Ronit, A.; Salem, M.; Laye, M.; Clausen, M. R.; Skogstrand, K.; Gerstoft, J.; Ullum, H.; Nielsen, S. D.
Abstract Altered T cell homeostasis in chronic hepatitis C virus (HCV) infection has been demonstrated. However, it is unknown whether fibrosis is associated with more perturbed T cell homeostasis in chronic HCV infection. The aim of this study was to examine and compare T cell subsets including recent thymic emigrants (RTE), naive, memory, senescent, apoptotic and IL‐7 receptor α (CD127) expressing CD4+ and CD8+ T cells as well as telomere length and interferon‐γ production in HCV‐infected patients with (n = 25) and without (n = 26) fibrosis as well as in healthy controls (n = 24). Decreased proportions of CD4+ and CD8+ RTE were found in HCV‐infected patients, especially in HCV‐infected patients with fibrosis (14.3% (9.7–23.0) and 28.8% (16.1–40.5), respectively) compared with healthy controls (24.2% (16.3–32.1), P = 0.004 and 39.1% (31.6–55.0), P = 0.010, respectively). Furthermore, HCV‐infected patients with fibrosis presented with a higher proportion of CD4+ T cells expressing CD127 compared with HCV‐infected patients without fibrosis [88.4% (84.5–91.0) versus 83.8% (79.9–86.8), P = 0.016]. Thus, impaired thymic output in HCV infection was found, and high proportion of CD127+ T cells may illustrate a compensatory mechanism to preserve T cell counts.